Factors Influencing the Work Quality of PT.United Motors Center Gresik Employees - Ramadhanty, Ika Wahyu (The International Journal of Business Review (The Jobs Review), 2023)
The purpose of this research is to analyze the factors that influence the quality of work results which include ethical orientation, professional commitment, audit experience, job satisfaction and motivation. This research method uses a type of qualitative research. The data analysis technique used in this research is data analysis arranged by Miles and Huberman. The results of the factors that affect the quality of work of employees at PT. United Motor Center Gresik in terms of internal factors are human resources, employee work experience, employee responsibilities, and employee capabilities. While the external factors are the environment, company leadership, work facilities, superiors' trust in subordinates, and salary. Job satisfaction affects the quality of work of employees at PT. United Motor Center Gresik. A comfortable work situation also makes a big contribution that can affect the quality of the employee's work itself.